Solar for all: A framework to deliver inclusive and environmentally sustainable solar irrigation for smallholder agriculture - Lefore, Nicole; Closas, Alvar; Schmitter, Petra S. (Elsevier, 2021)
Worldwide, off-grid solar photovoltaic irrigation is currently being developed with the expectation that it will help secure water access to increase food production, reduce fuel-based carbon emissions and energy costs, and increase human resilience to climate change. In developing countries across the Middle East and North Africa, South East Asia and Sub-Saharan Africa, the adoption of solar technology in agriculture to lift groundwater is rapidly expanding, following decreases in pump costs, economic incentives, and development partner initiatives. Solar irrigation potentially provides a cost-effective and sustainable energy source to secure food production and sustain livelihoods in line with multiple Sustainable Development Goals, but achieving such potential requires improved policies and institutions to coordinate across numerous stakeholders, objectives, and approaches. This paper uses cases and observations from across regions to propose a framework to support policy, regulation, and monitoring for environmentally sustainable and socio-economically inclusive solar irrigation investments. While not exhaustive, the components seek to address the intersection of energy, water and food security, as well as social equity. The paper emphasizes the need for an understanding of how solar irrigation can be scaled to be both accessible for smallholder farmers and environmentally sustainable.